Turning Waste into Wealth with Bricks Eco-Friendly in Indonesia - Rancaputra, Muhammad Hanifan; Abadi, Totok Wahyu (Indonesian Journal Publisher, 2024)
Plastic waste, especially from used bottles, poses significant environmental and health challenges due to its non-biodegradable nature. To address this, the 3R principles-Reduce, Reuse, and Recycle-are essential. This study introduces EcoBricks, made from used plastic bottles, as a sustainable solution to conventional building materials. Using a community-based participatory research approach, the project involves citizens in producing EcoBricks, aiming to foster environmental awareness and reduce the accumulation of plastic waste. The results show that EcoBricks provide a viable alternative to traditional bricks and raise ecological awareness among the community. The implications of this study underscore the potential of EcoBricks in sustainable construction, encouraging wider adoption and policy support for waste reduction initiatives.